Analiza dyskursu nad edukacją i rehabilitacją osób z niepełnosprawnością sprzężoną w Republice Czeskiej - Kasprzak, Tomasz (Kultura-Społeczeństwo-Edukacja, 2020)
Kasprzak Tomasz, Analysis of discourse on education and rehabilitation of people with disabilities coupled in the Czech Republic. Culture – Society – Education no 2(16) 2019, Poznań 2019, pp. 225–234, Adam Mickiewicz University Press. ISSN 2300-0422. DOI 10.14746/kse.2019.16.14. At the core of the Czech education system and rehabilitation for people with multiple disabilities to the assumption that this is a group that requires a specialized approach to this issue. The main purpose of the text is to present the organization of education of people with multiple disability in the Czech Republic. Education and rehabilitation with the participation of people with multiple disabilities encourages to undertake research related to the dynamics of changes as well as their size. This work is an attempt to show how various factors have shaped the current form of education of people with multiple disability in the Czech Republic.